Thermographic Insights into Degenerative Spinal Disorders: Evaluating the Diagnostic Potential of Digital Infrared Thermography Imaging - Sathish Muthu; Guna Pratheep Kalanchiam; Ashok Shyam (Journal of Orthopaedic Case Reports)
Degenerative spinal disorders are a growing concern, affecting millions worldwide and often leading to chronic pain, functional impairment, and reduced quality of life. Traditional imaging techniques such as magnetic resonance imaging and computed tomography scans primarily focus on structural abnormalities, limiting real-time physiological assessments. Digital infrared thermography imaging (DITI) has emerged as a promising non-invasive diagnostic tool that evaluates thermal emissions from the body, offering valuable insights into musculoskeletal dysfunction. This review explores the principles of DITI, its application in diagnosing degenerative spinal disorders, and its clinical implications. DITI operates on the principle that physiological disturbances – such as inflammation, neuropathy, and vascular irregularities –alter skin temperature distribution, which can be captured using infrared technology. It has shown promise in detecting conditions such as herniated discs, spinal stenosis, and facet joint degeneration by identifying abnormal thermal asymmetry. While DITI offers advantages such as real-time functional assessment, cost-effectiveness, and early disease detection, challenges related to standardization, environmental variability, and specificity persist. Recent advancements, including artificial intelligence-driven thermal analysis and hybrid imaging approaches, are improving DITI’s diagnostic precision and clinical utility. Establishing standardized protocols for environmental control, patient preparation, and image validation is crucial for ensuring reproducibility in spinal evaluations. As research progresses, integrating DITI with conventional imaging methods may enhance its role in clinical practice, optimizing diagnostic accuracy and treatment outcomes for patients with degenerative spinal disorders.